2012
DOI: 10.4103/0019-5154.94276
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral, skin, and oral and skin lesions of lichen planus in patients visiting a dental school in Southern India

Abstract: Background:Lichen planus (LP) is a mucocutaneous disease that is relatively common among adult population. LP can present as skin and oral lesions. This study highlights the prevalence of oral, skin, and oral and skin lesions of LP.Aims:The aim of this study was to evaluate the prevalence of oral, skin, and oral and skin lesions of LP from a population of patients attending the Department of Oral Medicine and Radiodiagnosis, Pushpagiri College of Dental Sciences, Tiruvalla, Kerala, India.Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 1 publication
2
38
1
5
Order By: Relevance
“…This was found to be similar to the study done by Omal et al among south Indian population was found to be similar to the present study. 18 Similarly by Mehdipour in their study reported increased prevalence of LP among patients of age group 40 to 60 yrs. 19 Among the patients with metabolic syndrome, maximum number of LP patients belonged to the sixth decade which was 7 (38.88%) of the 18 patients.…”
Section: Agementioning
confidence: 97%
“…This was found to be similar to the study done by Omal et al among south Indian population was found to be similar to the present study. 18 Similarly by Mehdipour in their study reported increased prevalence of LP among patients of age group 40 to 60 yrs. 19 Among the patients with metabolic syndrome, maximum number of LP patients belonged to the sixth decade which was 7 (38.88%) of the 18 patients.…”
Section: Agementioning
confidence: 97%
“…Os adultos, especialmente as mulheres (a proporção pode ser tão elevada como 3:1), são os mais acometidos. [6][7][8] O tratamento do LPO é paliativo e indicado apenas nos pacientes sintomáticos.…”
Section: A Organização Mundial De Saúde (Oms) Incluiu O Líquen Plano unclassified
“…O líquen plano oral (LPO) isolado é a forma mais comumente encontrada, enquanto o líquen plano cutâneo (LPC) isolado é a menos frequente [7].…”
Section: -Líquen Planounclassified
See 2 more Smart Citations